2021
DOI: 10.1097/iop.0000000000002049
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure and Glaucoma in Thyroid Eye Disease

Abstract: Purpose: Current literature lacks a summary of knowledge on intraocular pressure (IOP) elevation and glaucoma in thyroid eye disease (TED). This review aims to augment existing literature by providing such a summary. It qualitatively evaluates current knowledge on the pathogenesis, prevalence, and management of concomitant ocular hypertension or glaucoma in TED patients.Methods: In this narrative review, relevant publications were identified through a computerized database search. Search results were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…In contrast, other studies defined glaucoma based on history or examination findings, including intraocular pressure (measured using a variety of techniques), prescribed glaucoma medications, and glaucomatous visual field defects, among others. 6,16,24,27…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, other studies defined glaucoma based on history or examination findings, including intraocular pressure (measured using a variety of techniques), prescribed glaucoma medications, and glaucomatous visual field defects, among others. 6,16,24,27…”
Section: Discussionmentioning
confidence: 99%
“…Betzler et al 6 described how understanding the epidemiological connection between TED and glaucoma is challenging, as anterior segment disease among TED patients can make imaging and diagnosis of visual field defects difficult. Moreover, the comorbidity of dysthyroid optic neuropathy, which can affect 3%–7% of TED patients, 28 can be mistaken for glaucomatous visual field defects and obfuscates the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a population-based study of the elderly participants in the Blue Mountains Eye Study [ 67 ], thyroid dysfunction was found to be independently related to OAG. Other authors have mainly considered the relationship of thyroid-associated orbitopathy and glaucoma [ 68 ]. In our cohort, hypothyroidism or hyperthyroidism was present in 19% of the OHTG and 14% of the OAGG.…”
Section: Discussionmentioning
confidence: 99%